Choice of Functional Form and the Demand for Air Quality - Bender, Bruce; Gronberg, Timothy J.; Hwang, Hae-Shin (The Review of Economics and Statistics, 1980)
The quadratic Box-Cox approach is examined to determine its usefulness in demand research. In the absence of information about hedonic price and household demand structures, the flexible form is invaluable in both stages of the Rosen demand estimation procedure. The quadratic Box-Cox form permits a statistical investigation of a wide variety of specific hypotheses concerning specifications. Commonly-used functional forms in both the hedonic and demand stages are shown in the samples to be founded upon unacceptably restrictive hypotheses. The impact of changes in functional form upon demand-elasticity estimates and benefit estimates justify concern over the functional form-selection process. 8 references, 4 tables.